PLANNING PHASE 2 MULTICENTER RANDOMIZED TRIAL OF NEOADJUVANT CHEMO-RADIOTHERAPY FOLLOWED BY D2 GASTRECTOMY AND ADJUVANT CHEMOTHERAPY FOR LOCALLY ADVANCED GASTRIC CANCER - V. Yu. Skoropad; S. G. Afanasyev; S. V. Gamayunov; T. A. Agababyan; M. Yu. Volkov; S. A. Glushchenko; L. V. Evdokimov; K. S. Korchagina; S. A. Mozerov; O. A. Mikhaylova; N. O. Popova; G. O. Rukhadze; et al. (Сибирский онкологический журнал, 2016)
Introduction. The prognosis for surgical treatment of locally advanced gastric cancer remains disappointing. Neoadjuvant chemo-radiation therapy is relatively new and the least researched method of treatment, it is attracting more and more attention, mainly abroad in recent years. The aims of neoadjuvant therapy is the earliest start of systemic therapy, damage of the primary tumor and regional metastases, an increase in the percentage of radical operations, improving treatment outcome. Material and methods. The planning study is a multicenter, randomized clinical phase II trial. Patients of the first (experimental) group will be treated as the followes: neoadjuvant chemo-radiotherapy (total tumor dose of 46 Gy in 23 fractions with the concurrent modified CapOX scheme) followed by D2 gastrectomy and adjuvant chemotherapy. Patients of the second (control) group will be treated with D2 gastrectomy and adjuvant chemotherapy. Adjuvant chemotherapy will be carried out under the following schemes (optional for the researchers): CapOX or FOLFOX. Toxicity evaluation of neoadjuvant chemo-radiotherapy and adjuvant chemotherapy will be conducted with NCI CTC Toxicity Scale Version 3.0. The main objectives of the trial are to assess the safety and immediate effectiveness of neoadjuvant chemo-radiotherapy according to the criteria of the frequency and severity of postoperative complications and mortality, and tumor response. We are planning to include 80 patients with morphologically confirmed gastric cancer сT2–4N1–3, сT3–4N0–3; М0. The proposed trial will be carried out in accordance with the principles of the Helsinki Declaration, it has been approved by local ethic committees of the participated institutions. Results. As a result of this multicenter randomized trial it is planned to show the reproducibility of obtained in MRRC and a number of foreign centers results – that is, the safety and high immediate effectiveness of neoadjuvant chemo-radiotherapy in patients with locally advanced gastric cancer. Conclusion. If we reach the goals of the planning trial, the results would allow to reasonably recommend the start of large international phase III trials for the final evaluation of the proposed neoadjuvant treatment as a standard one in patients with locally advanced gastric cancer.